Emotional disturbances among diabetic patients in Malaysia - Al-Ani, Ali Sabri Radeef; Musa, Ramli; Nik Ahmad, Nik Nur Fatnoon (2013)

(untitled)
Background: Diabetes mellitus is a global health problem that causes significant mortality and morbidity. It is important to assess the association of diabetes with emotional disturbances symptoms like depressive, anxiety and stress symptoms so that we can detect early those psychiatric problems and treat them in order to have adequate glycemic control, less diabetic complications, improve quality of life, and good medication adherence . Despite this, emotional disturbances are consistently under-diagnosed and under-treated by physicians in general medical patients. Objectives: This study aims to determine the prevalence of emotional disturbances among patients with diabetes mellitus and to assess the severity of depressive symptoms among those patients.